Effect of company size and profitability on tax aggressiveness listed on the indonesia stock exchange - Surya Sanjaya; Parlindungan; Rahmat Hidayat; Edisah Putra Nainggolan; Gina Surna (Junal Ilmu Manajemen, 2023)
This study aims to determine the effect of company size and profitability partially and simultaneously on tax aggressiveness in pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2017-2021. The approach used in this study is quantitative. The population in this study is all registered pharmaceutical companies. on the Indonesia Stock Exchange (IDX) in 2017-2021. Sampling used purposive sampling method using certain criteria. The sample of this study was 10 companies from 12 companies. The analytical method used to test the hypothesis was to use multiple linear regression analysis. The results of the study show that partially firm size has no significant effect on tax aggressiveness. Profitability has a significant effect on tax aggressiveness. Then firm size and profitability have a significant effect on tax aggressiveness simultaneously.